PERKEMBANGAN HUKUM DI DUNIA DIGITAL : EVOLUSI HUKUM KEJAHATAN DUNIA MAYA - Dina, Dina Meilina; Zukriadi, Diki (LPPM Universitas Putera Batam, 2024)
This research explores the evolution of cybercrime law in the face of developments in informationand communication technology (ICT) over the last few decades. The development of digitaltechnology has provided countless benefits, but has also given rise to increasingly complex threatsin the form of cyber attacks and cybercrime. The aim of this research is to investigate howcybercrime law has evolved in response to changes in ICT and how these developments haveinfluenced the effectiveness of cybercrime law enforcement. This research also analyzes the roleof cross-border cooperation in cybercrime law enforcement and how developments in internationallaw have influenced countries' ability to deal with global cybercrime threats. The research resultsshow that the evolution of cybercrime law includes the establishment of more specific cybercrimelaws and stronger protection of personal data. Cross-border cooperation plays an important role incybercrime law enforcement, including information exchange, joint prosecution, asset freezing, andextradition. Developments in international law, such as the Budapest Convention and the GeneralData Protection Regulation (GDPR), have provided the necessary legal basis for more effectivecross-border cooperation. However, challenges remain, including legal and jurisdictionaldifferences between countries that often hamper law enforcement efforts. Therefore, increasinginternational cooperation and efforts to overcome these obstacles is crucial in maintaining securityand privacy in the ever-evolving digital era. This is because that cyber weaknesses can bedisastrous global threat that threatens the business sector, national security, behavior, childprotection, and government systems.The research results show that today's society still abusesocial media to spread crime in cyberspace.